Link between immunoexpression of hMLH1 and hMSH2 proteins and clinical-epidemiological aspects of actinic cheilitis - Dmitry José de Santana Sarmento; Gustavo Pina Godoy; Márcia Cristina da Costa Miguel; Éricka Janine Dantas da Silveira (Anais Brasileiros de Dermatologia, 2016)
Abstract: Background: The studies found in the literature associate the immunoexpression of hMLH1 and hMSH2 proteins with histologic aspects, but do not correlate it with clinical and epidemiological data. Objective: To evaluate the immunoexpression of hMLH1 and hMSH2 in actinic cheilitis, correlating it with clinical characteristics. Methods: We analyzed 40 cases. Histological and immunohistochemical analyses were performed. The following clinical variables were evaluated: gender, age range, ethnicity, clinical aspect and occupational sunlight exposure. Statistical evaluation included the Student t-test, while the significance level was set at 5%. Results: Greater immunoexpression of hMLH1 and hMSH2 was observed in females, individuals aged over 40, and mixed-race/black patients. Furthermore, the immunoexpression of these proteins was greater in actinic cheilitis with a white-colored appearance and in patients without occupational sunlight exposure. No statistical differences were observed for the variables studied. Conclusion: This study uncovered variations of hMLH1 and hMSH2 protein expression upon evaluation of clinical aspects in actinic cheilitis.